ALIGNMENT OF INTERNAL AND EXTERNAL BUSINESS AND INNOVATION DOMAINS - Katz, Bernard; Louw, Louis; du Preez, Niek (The South African Journal of Industrial Engineering, 2016)
“Instead of being really good at doing some particular thing, companies must be really good at learning how to do new things”. This ability to do new things involves both the identification and the mastery of the next ‘new thing’ as well as the ability to align the rest of the company with this new direction. This paper focuses on the alignment of innovation activities with the overall business strategy and infrastructure. An innovation strategic alignment model is presented that supports alignment in a company by identifying the driver of change and its impact on other areas of the business.